A Simple Assay for Quality Binders to Cucurbiturils. Issue 32 (7th July 2014) - Vázquez , Julián; Remón , Patricia; Dsouza, Roy N.; Lazar, Alexandra I.; Arteaga, Jesús F.; Nau, Werner M.; Pischel, Uwe
Abstract A new approach towards the rapid identification of quality binders to cucurbiturils—those that combine high affinity with high selectivity for a particular homologue—was developed. The assay exploits macrocycle‐specific optical fingerprints (colorimetric or fluorimetric) of carefully selected indicators dyes. The screening of a guest library revealed known (e.g., adamantane derivatives) and new (e.g., terpenes) quality binders. The predictive power of the assay was underpinned by the modeling of the involved thermodynamic equilibria.